Fatigue Strength Assessment of AlSi7Cu0.5Mg T6W Castings Supported by Computed Tomography Microporosity Analysis. (2016) - Garb, C.; Leitner, M.; Grün, F.
Abstract: The fatigue strength of the casted aluminum alloy AlSi7Cu0.5Mg T6W is investigated, whereat different eutectic modifiers, Sr and Na, are used for the two fatigue testing series. The tested specimens are extracted from three different locations of casted cylinder heads. The high-cycle fatigue testing is executed with cylindrical specimens at a load ratio of R = -1. The investigations are supported by CT-scans of the specimens and a comprehensive fractographic analysis. The obtained micro pore sizes from CT-scans are compared with thus of the fractography. It is shown that the maximum micro pore sizes near the surface of both examinations are comparable. The database is statistically evaluated using extremal distribution based functions. To assess the fatigue strength of the imperfected specimen, the simplified crack propagation based approach according to Tiryakioglu is applied. The cumulative distribution function matches well to the experimental results. This methodology features the incorporation of extremal micro pore sizes into finite life fatigue strength.